2013
DOI: 10.1097/ccm.0b013e31827585fe
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Attitudes Toward Donation After Cardiac Death Among Healthcare Providers and the General Public*

Abstract: Identified themes were the levels of support for DBD vs. DCD, attitudes toward postmortem measures without previous consent, lack of knowledge about DCD, concerns about the Dead Donor Rule, the potential for conflict of interest, making donation happen, and the call for standardized DCD protocols. All of these issues are of ethical relevance and merit further discussion. We conclude that deep-rooted concerns about DCD exist among medical personnel and the general public. These need to be taken seriously in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 33 publications
4
53
0
3
Order By: Relevance
“…11 Some reviews have compared the knowledge and attitudes of nurses toward organ donation across countries; 9 others have synthesized the literature on the attitudes of these professionals towards brain death and organ donation; 8 some others have reviewed research on attitudes of medical personnel toward organ donation in the case of cardiac death. 12 In spite of this progress, to date there has been no encompassing overview of the work on health care professionals' perspectives on the organ donation and transplant processes; in particular, no account has been taken of publications in languages other than English. The latter is important because non-English speaking countries, such as Spain, Portugal and Brazil, have made significant advances in organ donation and transplantation and in publishing their experience.…”
Section: Introductionmentioning
confidence: 99%
“…11 Some reviews have compared the knowledge and attitudes of nurses toward organ donation across countries; 9 others have synthesized the literature on the attitudes of these professionals towards brain death and organ donation; 8 some others have reviewed research on attitudes of medical personnel toward organ donation in the case of cardiac death. 12 In spite of this progress, to date there has been no encompassing overview of the work on health care professionals' perspectives on the organ donation and transplant processes; in particular, no account has been taken of publications in languages other than English. The latter is important because non-English speaking countries, such as Spain, Portugal and Brazil, have made significant advances in organ donation and transplantation and in publishing their experience.…”
Section: Introductionmentioning
confidence: 99%
“…The vast major ity, 112 (94.1% of respondents), reported that their institution (which might represent two or more hospitals) had, on at least one occasion, referred a patient for DCD. The majority, 93 (78.1% of respondents), had a local protocol for DCD, as is suggested in National Guidance (5), yet despite this, 89 (74.7% of respondents) desired a more detailed/proscriptive national protocol, which is a recurrent theme in similar surveys (9).…”
mentioning
confidence: 93%
“…However, the determination of futility is probabilistic, of variable reliability, and, at least in part, is subjective and related to beliefs regarding the quality and sanctity of life. Furthermore, there are isolated anecdotes of significant and even miraculous recovery following the dec laration of futility, making such arguments and the practice of DCD highly controversial (9). On the other hand, such inter ventions are arguably unpleasant/burdensome to the individ ual, of no benefit to them and might potentially protract their dying process, with the unintended result that organ retrieval, to which consent has been obtained, cannot occur within the acceptable (limited) time frame following withdrawal of sup portive therapies.…”
mentioning
confidence: 98%
“…While surveys show widespread general support in the United States for organ donation, this support is not necessarily deep or stable (Bastami et al 2013;Doig and Zygun 2008;Seltzer et al 2000;Volk et al 2010). Evidence suggests that the public is poorly informed regarding the different types of organ donation and how these differences may impact the donation process and end-of-life care.…”
mentioning
confidence: 94%
“…Furthermore, there is general consensus that organ donation and any related procedures should be predicated on prior knowledge of the person's wishes or the consent of their family (Siminoff et al 2001). Many individuals also harbor concerns about how organ donation decisions are made and the potential for conflicts of interests in weighing the interests of donors and potential recipients (Bastami et al 2013;Seltzer et al 2000). All of these issues run the risk of undermining public trust in the organ donation process (Truog 2008).…”
mentioning
confidence: 97%